Faith and Modernity: Navigating the Intersection of Islam, Secularism, and International Relations in Contemporary Turkish Society - Damayanti, Rizki; Ardabili, Farzad Sattari (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
This research investigates the intricate relationship between Islam, secularism, and international relations in contemporary Turkish society, focusing on how these dynamics shape social norms, values, and Turkey's global engagements. Positioned as a predominantly Muslim nation with a secular constitution, Turkey offers a unique context for examining the influence of religious and secular forces on both domestic life and foreign policy. This qualitative study employs an analytical framework that integrates realist and constructivist perspectives, allowing for a comprehensive exploration of religious authorities, cultural expressions of faith, gender roles, political Islam, economic activities, and interfaith relations. The findings reveal that Islam significantly shapes social and cultural practices in Turkey, creating a complex interplay with the country's secular policies. This dynamic also extends to Turkey's foreign policy, where religious and secular considerations influence its diplomatic strategies and international image. The study concludes that understanding this balance is crucial for comprehending Turkey's domestic and global actions, particularly as they navigate geopolitical tensions and alliances. This research contributes to the broader discourse on the interaction between religion and state, offering insights into how Turkey's approach to Islam and secularism provides insights that could be relevant to other nations facing similar challenges. The conclusions drawn underscore the importance of maintaining a nuanced perspective on the coexistence of faith and modernity in shaping national identity and international relations.